THE ABNORMALITY MORPHOLOGY OF Namalycastis (POLYCHAETA: NEREIDIDAE) FROM JAKARTA BAY AND ESTUARY WAY BELAU LAMPUNG - Sevi Sawestri (Pusbindiklat - LIPI, 2013)
Namalycastis (Polychaetes: Nereididae) lives in estuarine that can be used as polluted bioindicators. Morphological abnormalities in some Polychaeta members have been found previously, whereas the abnormality Namalycastis from Indonesia has never been recorded. The aim of this research was to study the abnormality morphology of Namalycastis form Jakarta Bay (polluted sediment) and estuary Way Belau-Lampung (unpolluted sediment). There were two species of Namalycastis in both locations, i.e. N. abiuma and N. cf borealis. The abnormality of Namalycastis collection from both locations consist of five structures i.e. on antenna appendages, eyes, tentacular cirri, parapodia, and setae. The abnormality of Namalycastis collection from Jakarta Bay was higher than from Way Belau. The abnormality of parapodia and setae in this research might had resulted from the influence of polluted habitat conditions.